2016
DOI: 10.1038/cddis.2016.236
|View full text |Cite
|
Sign up to set email alerts
|

Golgi-associated LC3 lipidation requires V-ATPase in noncanonical autophagy

Abstract: Autophagy is an evolutionarily conserved catabolic process by which cells degrade intracellular proteins and organelles in the lysosomes. Canonical autophagy requires all autophagy proteins (ATGs), whereas noncanonical autophagy is activated by diverse agents in which some of the essential autophagy proteins are dispensable. How noncanonical autophagy is induced and/or inhibited is still largely unclear. In this study, we demonstrated that AMDE-1, a recently identified chemical that can induce canonical autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…As seen from the representative blots, and consistent with the known ability of ConA and other V-ATPase inhibitors to stall autophagic flux [47], ConA treatment increased total LC3B, mainly as LC3B-II in Panc-1 cells and LC3B-I in BxPC-3 cells, and increased p62 in both cell lines ( Figure 5A-C). A requirement for V-ATPase activity for LC3 lipidation, as seen in BxPC-3 cells, is a hallmark of unconventional autophagy [48], and this finding seems consistent with a previous report of differential regulation of LC3 lipidation in BxPC-3 and Panc-1 cells [49]. a3 KD modestly increased LC3B-II/LC3B-I in both cell types ( Figure 5D,E), with little if any change in p62 ( Figure 5D,F).…”
Section: V-atpase Inhibition Increases Hif-1α Protein Level Ampk Actsupporting
confidence: 92%
“…As seen from the representative blots, and consistent with the known ability of ConA and other V-ATPase inhibitors to stall autophagic flux [47], ConA treatment increased total LC3B, mainly as LC3B-II in Panc-1 cells and LC3B-I in BxPC-3 cells, and increased p62 in both cell lines ( Figure 5A-C). A requirement for V-ATPase activity for LC3 lipidation, as seen in BxPC-3 cells, is a hallmark of unconventional autophagy [48], and this finding seems consistent with a previous report of differential regulation of LC3 lipidation in BxPC-3 and Panc-1 cells [49]. a3 KD modestly increased LC3B-II/LC3B-I in both cell types ( Figure 5D,E), with little if any change in p62 ( Figure 5D,F).…”
Section: V-atpase Inhibition Increases Hif-1α Protein Level Ampk Actsupporting
confidence: 92%
“…However, it should be noted that the relationship between V‐ATPase and autophagy is complex particularly as the V‐ATPase has a well‐established role in activation of lysosomal acid hydrolases that mediate proteolysis during autophagy 80, 81, 82. Moreover, although V‐ATPase inhibition can result in increased autophagic markers in some settings,74 V‐ATPase is required for activation of noncanonical autophagy 83. In a very recent study, the autophagy‐related protein ATG5 was demonstrated to displace ATP6V1E1 from V‐ATPase, causing it to accumulate in exosomes 84.…”
Section: V‐atpase As a Potential Cancer Therapeutic Targetmentioning
confidence: 99%
“…During amino acid or glucose starvation, membrane recruitment of ATG16L1 involves its binding to WIPI2b 11 , an effector protein of phosphatidyl 3-phosphate (PI(3)P) or PI(5)P 12,13 . However, ATG16L1 targeting to membranes may be independent of WIPI2b during endomembrane LC3 lipidation [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%